What's the Issue ? Remarques partisanes sur les études littéraires dans leur rapport aux études culturelles - Schuerewegen, Franc (Verbum – Analecta Neolatina, 2012)
Cultural studies and literary studies are sometimes in conflict with each other, but why? They can be in good understanding with each other if we give it a try. Why can they not be brothers and sisters, and work in team? I try to explain here why good understanding is feasible, as far as methodology is concerned. But I admit, I am a bit sceptical, too. I argue that good friends can also be good enemies, but can work together nonetheless.